2020
DOI: 10.1002/er.5643
|View full text |Cite
|
Sign up to set email alerts
|

Vibration‐based piezoelectric, electromagnetic, and hybrid energy harvesters for microsystems applications: A contributed review

Abstract: Wireless sensor nodes (WSNs) and embedded microsystems have recently gained tremendous traction from researchers due to their vast sensing and monitoring applications in various fields including healthcare, academic, finance, environment, military, agriculture, retail, and consumer electronics. An essential requirement for the sustainable operation of WSN is the presence of an uninterrupted power supply; which is currently obtained from electrochemical batteries that suffer from limited life cycles and are ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(54 citation statements)
references
References 171 publications
(256 reference statements)
0
53
0
1
Order By: Relevance
“…Furthermore, hybrid nanogenerators were also found to have promising energy harvesting capabilities. Hence, many researchers have attempted to fabricate hybrid nanogenerators to harness synergy and improve output performance 26‐29 . In order to leverage the advantages of both piezoelectric and triboelectric nanogenerators, the piezoelectric‐enhanced triboelectric bio‐nanogenerators (P‐TENGs) were proposed for efficient mechanical energy harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hybrid nanogenerators were also found to have promising energy harvesting capabilities. Hence, many researchers have attempted to fabricate hybrid nanogenerators to harness synergy and improve output performance 26‐29 . In order to leverage the advantages of both piezoelectric and triboelectric nanogenerators, the piezoelectric‐enhanced triboelectric bio‐nanogenerators (P‐TENGs) were proposed for efficient mechanical energy harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this technology is not limited to theoretical predictions. In the review work of Iqbal et al [4], they concluded that due to the large amount of vibration-based energy available in the environment, the VEH has been identified as the energy harvester with the highest potential. Recently, Jiang et al [5] also reviewed the piezoelectric vibration energy harvesting technologies with magnetic coupling and determine the potential benefits of the magnetic force on energy-harvesting techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The energy transducer converts energy from the physical domain to the electrical domain, generating a source-dependent output signal [ 10 , 11 ]. For kinetic energy harvesting, electromagnetic and piezoelectric energy transducers are common choices, which create an alternating current (AC) output [ 1 , 7 , 12 , 13 , 14 ]. The intended system loads are commonly low-power electronic systems, such as Internet of Things (IoT) nodes or sensing systems, requiring a direct current (DC) input [ 9 ].…”
Section: Introductionmentioning
confidence: 99%